(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Eco-tourism is one of the fastest growing industries. Eco-tourism is often perceived as a tool for promoting sustainable development in developing countries. Arunachal Pradesh “the land of dawn-lit mountains” has unparalleled natural beauty with extensive geographical diversity and climatic conditions varying from the tropical to the temperate having a variety of wildlife, flora and fauna. Objective: The paper aims to find out the potentiality of eco-tourism in Arunachal Pradesh. Methodology: This study is descriptive type in nature based basically on data of secondary sources collected especially from published books, journals, official reports, and websites. Conclusion: Tourism industry can play a vital role in the State. As this sector is a labor-intensive industry, it can open an employment opportunity. A large number of unemployed persons can be employed by this industry. The Government should take necessary steps for development of the industry.